2004
DOI: 10.1002/macp.200300067
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design, Synthesis and Properties of Novel Polyurethanes Containing Tetracyanocyclopropyl Groups as Piezoelectric Chromophores

Abstract: Summary: 1‐(2′,2′,3′,3′‐Tetracyanocyclopropyl)‐3,4‐di‐2′‐hydroxyethoxybenzene (4) was prepared by the reaction of bromomalononitrile with 3,4‐di‐(2′‐hydroxyethoxy)benzylidenemalononitrile (3). The dipole moment of diol 4, calculated by the ASED‐MO method, was 4.01 D. Diol 4 was condensed with 2,4‐toluenediisocyanate and 3,3′‐dimethoxy‐4,4′‐biphenylenediisocyanate to yield polyurethanes 5 and 6 containing tetracyanocyclopropane functionalities in the side‐group. The resulting polymers 5 and 6 were soluble in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…More recently, Petroff et al used the same strategy and created polar molecules doped polydimethylsiloxane (PDMS) foams and measured the electrical and mechanical properties and by tuning these properties they achieved a maximum d 33 piezo-coefficients about 153 pCN −1 [4]. Furthermore, many researchers showed that the inclusion of polar molecules in polyurethane can create either high piezoelectricity or NLO materials [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. We motivated by reviewing the previous works to do further experiments to observe the effect of polar moieties on other properties of polyurethane.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Petroff et al used the same strategy and created polar molecules doped polydimethylsiloxane (PDMS) foams and measured the electrical and mechanical properties and by tuning these properties they achieved a maximum d 33 piezo-coefficients about 153 pCN −1 [4]. Furthermore, many researchers showed that the inclusion of polar molecules in polyurethane can create either high piezoelectricity or NLO materials [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. We motivated by reviewing the previous works to do further experiments to observe the effect of polar moieties on other properties of polyurethane.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 5(b), many parts have been protruded out from the surface after Corona poling, implying that urethane linkage of the cholesteric side chain has been interacted with the applied electrical voltage. Thus the polymer surface has been changed dramatically after poling, resulting in numerous hills and valleys in the surface structure, which were aligned to the poling direction (28,29). During poling mainly side chain alignment is possible as its length is very small compared to that of the main chain and is free for movement (30).…”
Section: P-e Hysteresis For Poled and Unpoled Samplesmentioning
confidence: 98%
“…6À8 One is to employ chemical crosslinking method [9][10][11][12][13] and the other is to utilize high glass transition temperature (T g ) polymers as matrix such as polyimides. Since polyurethane matrix with extensive hydrogen bonding between urethane linkages can form physical crosslinking system, [20][21][22][23][24] we choose this physical crosslinking system as polymer matrix to investigate the alignment stability of materials. For the chemical crosslinking method, the crosslinking temperature (T c ) has to be higher than T g to ensure an efficient poling of the chromophores before the crosslinking reaction starts.…”
Section: Introductionmentioning
confidence: 99%